Linguistic Geoengineering: A New Paradigm for Discursive Infrastructure and Public Persuasion - San Jose, Dominic Bryan (Linguistic Exploration, 2026)
This theoretical paper (1) defines linguistic geoengineering as a theoretical framework, (2) distinguishes its unique characteristics from established theories of language and power, and (3) analyzes its implications for public persuasion and democratic engagement. Linguistic geoengineering, a novel framework for analyzing language, power, and public influence, is defined as the deliberate, systematic restructuring of discourse environments with the goal of shaping collective perception, behavior, and decision-making. A typology is developed—metaphoric, narrative, lexical, and infrastructural engineering—demonstrating how linguistic practices can recalibrate collective perception, behavior, and decision-making. It addresses three overlooked aspects in current scholarship: intentionality, scale, and systemic impacts. This paradigm conceptualizes language as an engineerable environment, facilitating the analysis of how various actors, including states and activists, craft linguistic interventions to impact public life. However, this reframing presents ethical and methodological issues. How can scholars differentiate between organic discourse shifts and artificially constructed ones? What measures should be implemented to avert the misuse of language interventions? In what ways could the public oppose or counteract such interventions? Future studies must address these inquiries by formulating methodologies for identifying linguistic geoengineering in practice, analyzing its function across many crises and domains, and scrutinizing its normative consequences. This paradigm necessitates viewing language not only as a reflection of society but as a domain of design and conflict, where the contention over words represents a contest over futures.